How MNC's subsidiaries may improve their innovative performance? The role of external sources and knowledge management capabilities. Issue 3 (8th May 2017) - Ferraris, Alberto; Santoro, Gabriele; Dezi, Luca
Abstract : Purpose: This paper aims at exploring the effect of knowledge management (KM) practices on the relationship between external research and development (R&D) and innovative performance. The authors argue that the firms which develop and possess superior KM capabilities have the ability to better manage external knowledge and combine it with the internal one. Design/methodology/approach: The authors used a sample of 117 European MNC subsidiaries. An OLS regression analysis was carried out to evaluate the moderator effect of KM on the relationship between external R&D and innovative performance. Findings: The authors found positive evidences in favor of a moderator effect of KM. This means that subsidiaries with superior KM capabilities are more effective in using external R&D, augmenting the magnitude of their external sources of knowledge and, consequently, improving their innovative performance. Practical implications: Managerially speaking, both corporate and subsidiaries' managers need to understand the relevance of managing knowledge effectively and efficiently at the subsidiary level. Corporate managers need to allocate more resources (both financial and managerial) to the subsidiaries that are active in knowledge transfer and sharing, while subsidiaries managers need to implement practically the KM tools and processes at the subsidiary organizational level to improve subsidiary's innovative performance. Originality/value: This paper contributes mainly to the KM field, highlighting the importance of KM at the subsidiary level, whereas most of previous studies focus on different units of analysis.